2017
DOI: 10.5964/psyct.v10i1.200
|View full text |Cite
|
Sign up to set email alerts
|

Aristotle’s concept of mental imagery in sports

Abstract: Throughout the past decade, there has been an accelerated expansion of heightening consciousness in athletic performance's mental facets, which is reflected in the aggrandizement of research concern in cognitive sports psychology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Çünkü duyum ile düşünce arasında bulunan imgeleme yetisini, sporcunun etkin biçimde kullanabilmesi oyunlarda başarılı olmasına yol açacaktır. 19 Burada fantazya, adeta sporcunun rakibinin oyununda görmesi gereken stratejileri aydınlatan ve bu bilgilerle oyun kurmasına imkan veren bir yeti olarak anlaşılabilir. Ona göre jimnastikle bedensel yapının yanı sıra insan hareketlerinin de forma girmesi ve ölçülü olmayı alışkanlık edinmesi, akılyürütmelerinin öğretildiği zihinsel gelişimde kolaylık sağlanacaktır.…”
Section: Anti̇k çAğda Sporunclassified
“…Çünkü duyum ile düşünce arasında bulunan imgeleme yetisini, sporcunun etkin biçimde kullanabilmesi oyunlarda başarılı olmasına yol açacaktır. 19 Burada fantazya, adeta sporcunun rakibinin oyununda görmesi gereken stratejileri aydınlatan ve bu bilgilerle oyun kurmasına imkan veren bir yeti olarak anlaşılabilir. Ona göre jimnastikle bedensel yapının yanı sıra insan hareketlerinin de forma girmesi ve ölçülü olmayı alışkanlık edinmesi, akılyürütmelerinin öğretildiği zihinsel gelişimde kolaylık sağlanacaktır.…”
Section: Anti̇k çAğda Sporunclassified
“…The free throw is the easiest shot for many reasons, but it sometimes may be very difficult because of the various pressures of the game, emotional stress, and its accompanying responses [9]. Researchers [10,11] found that professional basketball shooters predict free-throw outcomes with higher accuracy than non-elite players when watching video clips (MI) of free throws. As a consequence, shooting accuracy affects on the match's outcome in all types of games and sports [12] and this outcome can improve significantly if physical exercise is combined with mental imagery, according to researcher [13].…”
Section: Introductionmentioning
confidence: 99%